DAMPAK EFESIENSI PENGGUNAAN TEKNOLOGI DALAM PENINGKATAN SKALA PRODUKSI PETANI PADI KABUPATEN NAGAN RAYA - Uci Marlianda; Rollis Juliansyah (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2022)
This research was carried out to determine the impact of efficient use of technology in increasing the production scale of farmers in Nagan Raya Regency. Primary data and secondary data are the data used in this research, where the data used is in the 2010-2020 period. Direct interviews with rice farmers are the technique used to collect primary data while secondary data is obtained from the Central Statistics Agency (BPS) and regional agencies. The linear regression analysis model is used as a data analysis model to analyze the use of technology that influences rice production. The results of the research show that the use of technology has a real influence on increasing rice production in East Seunanagn District, Ngan Raya Regency. Based on the regression of the harvest area variable individually, the harvest area variable has a significant effect on the productivity of the harvest, rice availability in Nagan Raya Regency.